Ok I have been trying to figure this out for a couple of days now and seem to be stumped. I know it is a fairly simple problem I just can't get it to click! Anyways, here is my problem: I have a Eulerian velocity of V1 = k*z1 and I want to show that this equals z1 = x1*e^k(t-t0), which is the Lagrangian motion. This is a problem from my continuum mechanics book. I know that if I solve for the equation (dz1/dt) + z1^2 = 0, with V1 = dz1/dt and initial boundary conditions of z1=x1 at t=0, then I should get the answer, but I am having no luck. Does anyone know how to convert from Eulerian Velocity, V1 = k*z1, and get the Lagrangian motion, z1 = x1*e^k(t-t0)? Thanks for any help you can provide.